N‐terminomics and proteogenomics, getting off to a good start. Issue 23 (23rd September 2014) - Hartmann, Erica M.; Armengaud, Jean; Pandey, Akhilesh; Pevzner, Pavel A.
<x xml:space="preserve">Abstract</x> Proteogenomics consists of the annotation or reannotation of protein‐coding nucleic acid sequences based on the empirical observation of their gene products. While functional annotation of predicted genes is increasingly feasible given the multiplicity of genomes available for many branches of the tree of life, the accurate annotation of the translational start sites is still a point of contention. Extensive coverage of the proteome, including specifically the N‐termini, is now possible, thanks to next‐generation mass spectrometers able to record data from thousands of proteins at once. Efforts to increase the peptide coverage of protein sequences and to detect low abundance proteins are important to make proteomic and proteogenomic studies more comprehensive. In this review, we present the panoply of N‐terminus‐oriented strategies that have been developed over the last decade.